Low‐complexity 0.55‐V 2.5‐μW bandgap reference and power‐on reset hybrid circuit. Issue 5 (1st March 2016) - Zhou, Bo; Liu, Shuli; Chiang, Patrick
Abstract : A near‐threshold low‐complexity bandgap reference (BGR) and power‐on reset (POR) hybrid circuit is implemented in 65 nm CMOS, with an ultra‐low supply voltage of 0.55 V and power consumption of 2.5 μW. The BGR employing amplifier offset voltage and current matching, and the POR based on offset voltage matching and loop settling feature, are proposed. The circuit‐level simulation results verify that the presented implementation, not only generates a stable reference voltage with the typical temperature coefficient of 120 ppm/°C and line‐regulation feature of 3.3%/V, but provides a robust reset signal with power‐on and brown‐out detection function. The proposed near‐threshold circuit has ultra‐low power supply and design complexity, both for BGR and POR modules, when compared to the reported.